Should Market Value Be Retained as the Only Tax Base for Municipal Property Rates in South Africa? - Franzsen, R (Potchefstroom Electronic Law Journal, 2022)
In terms of the Local Government: Municipal Property Rates Act 6 of 2004 (MPRA), metropolitan and local municipalities in South Africa may levy property rates on property. The MPRA provides for only one tax base, namely "market value". Given the paucity of skills and capacity to prepare credible valuation rolls and given the costs of doing so, especially B3 and B4 local municipalities situated in rural areas are struggling to comply with the valuation-related provisions of the MPRA. A brief review of property tax base options utilised globally indicates that some countries allow for different tax bases (or even different taxes) on the basis of the location and/or use of property and some jurisdictions apply simplified methodologies (such as value banding, points-based assessment or even self-assessment) to assess properties for property tax purposes. In the light of there being viable alternatives to market value and of the challenges faced by many rural local municipalities, the South African government should revisit the policy decision to have only market value as the tax base across vastly different types of municipalities.